Kejadian Burnout Syndrome pada Perawat di Surabaya: Studi Analisis Faktor - Habsari, Dyah Unggul Putri; Widyawati, Ika Yuni; Hidayati, Laily; Nursalam, Nursalam (Universitas Muhammadiyah Surabaya, 2021)
Introduction: Burnout syndrome is still a problem related to nurses' psychology, especially during the current COVID-19 pandemic. Burnout syndrome can be influenced by interpersonal and environmental factors of a person. The purpose of this study was to analyze the relationship between personality, workload and appreciation of burnout syndrome in nurses who treat COVID-19 patients at the Indrapura Field Hospital, Surabaya. Methods: This study uses a descriptive analytic design with a cross sectional approach. The number of samples was 42 respondents who were taken using a non-probability sampling technique, namely purposive sampling. Analysis using Spearmen Rho test. Result: The results showed that there was a relationship between workload (p = 0.034; r = 0.327) and rewards (p = 0.039; r = -0.320) with burnout syndrome in nurses treating COVID-19 patients at the Indrapura Field Hospital Surabaya. There was no relationship between personality (p=0.244;r=-0.184) and burnout syndrome in nurses who treated COVID-19 patients at the Indrapura Field Hospital, Surabaya. Conclusion: Burnout syndrome in nurses who treat COVID-19 patients at the Indrapura Field Hospital Surabaya is related to workload and rewards. Personality factors with positive attitudes are not necessarily able to prevent someone from experiencing burnout syndrome. So that this research can be used as an illustration for nurses during the current COVID-19 pandemic and situations in the future.